A pure DNA hydrogel with stable catalytic ability produced by one-step rolling circle amplification. Issue 21 (27th February 2017) - Huang, Yishun; Xu, Wanlin; Liu, Guoyuan; Tian, Leilei
Abstract : Rolling circle amplification for cost-effective and facile fabrication of a pure DNA hydrogel with highly improved catalytic stability. Abstract : A rolling-circle-amplification method was developed to produce DNA hydrogels with horseradish-peroxidase-like catalytic capability. The catalytic hydrogel exhibits highly improved stability at elevated temperatures or during a long-term storage. Integrated with glucose oxidase, the complex hydrogel can be applied to the sensitive and reliable detection of glucose.